Restraining the Cr-Zr interdiffusion of Cr-coated Zr alloys in high temperature environment: A Cr/CrN/Cr coating approach. (15th April 2023) - Yang, Jianqiao; Shang, Lunlin; Sun, Jiyuan; Bai, Shuyuan; Wang, Shuzhong; Liu, Junkai; Yun, Di; Ma, Dayan
Abstract: In this study, a Cr-CrN-Cr coating was fabricated on Zr alloys to restrain the Cr-Zr interdiffusion of Cr-coated Zr alloys. The early stage diffusion, decomposition, and oxidation behaviors of the coating sample are investigated by a tube furnace equipped with a "fast-in & fast-out" tool. The outer and inner Cr layer was transferred into Cr2 N by nitrogen, which was formed by the decomposition of the CrN layer. A Zr2 N layer formed at the interface between the residual coating and Zr substrate, which acted as a diffusion barrier. After oxidation in a steam environment, the coating structure can be divided into Cr2 O3, CrN, Cr2 N, and Zr2 N (from outside to inside). Highlights: Cr-CrN-Cr coating designed to restrain Cr-Zr interdiffusion. Zr2 N interlayer acted as a diffusion barrier. Excellent oxidation resistance of specimens at 1400 °C steam obtained. Crud deposition rate drastically decreased on coating surface.